Inhibition of beta-myosin heavy chain gene expression in pressure overload rat heart by losartan and captopril - Ling Qi; Chen Tie-Hua; Guo Zhao-Gui (Acta Pharmacologica Sinica, 2016)
AIM: To study the effects of losartan and captopril on beta-myosin heavy chain (MHC), and alpha-MHC gene expression. METHODS: Pressure overload was produced by abdominal aortic coarctation (AAC) in rats. alpha- and beta-MHC mRNA were measured by Northern blot. RESULTS: In left ventricular myocardium of sham-operated rats, the alpha-MHC mRNA predominated, while the beta-MHC mRNA was only detectable. In response AAC, there was a 70-fold increase in the beta-MHC mRNA (P < 0.01), while alpha-MHC mRNA reduced to 26% (P < 0.01). Losartan (3 mg.kg-1.d-1, i.g. for 11 d) to AAC rats caused inhibitions of beta-MHC by 96% and alpha-MHC by 86% gene expression without lowering blood pressure. A reduction in beta-MHC mRNA was also seen in captopril-treated rats (30 mg.kg-1.d-1, i.g. for 11 d), but the inhibitory effect of captopril on alpha-MHC mRNA was less than that of losartan (44% vs 86%, P < 0.05). CONCLUSIONS: The shift of MHC isoform induced by pressure overload is due to up-regulation of beta-MHC and down-regulation of alpha-MHC gene expression. Inhibition of beta-MHC gene expression by losartan is achieved primarily by direct blockade of angiotensin II type I receptors in the myocardium, independent on hemodynamics.